2010
DOI: 10.1177/0145721709358460
|View full text |Cite
|
Sign up to set email alerts
|

Self-care Beliefs and Behaviors in Ugandan Adults With Type 2 Diabetes

Abstract: Results from this study highlight the challenges of diabetes self-care in resource-poor countries. Improving diabetes care will require systems-level interventions to provide access to basic resources as well as to social support and educational interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 14 publications
2
34
0
3
Order By: Relevance
“…The review was restricted to manuscripts written in English. In total, 15 articles consisting of eight qualitative (2633) and seven quantitative studies (3440) met the inclusion criteria and were included in this review. Figure 1 shows the flow of included studies in this review.…”
Section: Resultsmentioning
confidence: 99%
“…The review was restricted to manuscripts written in English. In total, 15 articles consisting of eight qualitative (2633) and seven quantitative studies (3440) met the inclusion criteria and were included in this review. Figure 1 shows the flow of included studies in this review.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of one article used the Household Food Insecurity Access Scale (HFIAS), a measure of food accessibility developed by the US Agency for International Development and validated for use in developing countries [39•]. However, scholars have identified the need to develop culturally relevant, globally appropriate measures that take into account typical local foods, as well as meal sizes and frequency [40]. Of the reviewed articles, four used qualitative methods, 26 used quantitative methods, and three used mixed methods.…”
Section: Review Methodsmentioning
confidence: 99%
“…In study conducted in Nigeria to evaluate the level of knowledge among type 2 diabetics showed that knowledge is below mean score 39% ± 16.7% [62]. In a South African primary care setting, showed lower levels of diabetes knowledge with an average of 52.2% compared to their Indian counterparts with an average of 75.9% [63,64].…”
Section: Idf Atlasmentioning
confidence: 99%